2020
DOI: 10.3390/vaccines8020238
|View full text |Cite
|
Sign up to set email alerts
|

Measures to Improve Influenza Vaccination Coverage in Spanish Medical Students

Abstract: Objective: To find out what measures medical students believe could help improve their influenza vaccination coverage. Method: On 5 November 2019, the Dean of the Zaragoza Medical School sent an e-mail to the students asking them to fill out a questionnaire through Google Forms, in which they were asked to describe, in an open field, the measures that they believed could contribute to improving their flu vaccination coverage. The content of the responses was analyzed in a classic way, extracting descriptors an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 21 publications
0
4
0
1
Order By: Relevance
“…It may therefore be more important to educate students about influenza itself rather than about vaccination, emphasizing that influenza poses a serious health risk for certain patients and there is an ethical imperative to protect them from infection. Knowledge of barriers and addressing them in education and strategic activities are crucial to convince “vaccine hesitant” individuals [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…It may therefore be more important to educate students about influenza itself rather than about vaccination, emphasizing that influenza poses a serious health risk for certain patients and there is an ethical imperative to protect them from infection. Knowledge of barriers and addressing them in education and strategic activities are crucial to convince “vaccine hesitant” individuals [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, in our study, fewer than 1% of participants reported that flu vaccination was promoted at university. In a Spanish study, the students themselves suggested that vaccination should be performed at the medical school itself, i.e., in the building where they receive their classes, rather than in a health care setting [31].…”
Section: Discussionmentioning
confidence: 99%
“…The responses to the questionnaires were converted to electronic form by the first author; the output was double checked and analyzed by both authors independently. The content of the survey was analyzed in a classical way, grouping the most common student responses; before grouping, the key descriptors were extracted from the responses to open questions and labelled appropriately [31].…”
Section: Methodsmentioning
confidence: 99%
“…Alguns trabalhos referem que, além da cobertura vacinal na PHIV ser baixa para algumas vacinas, a sua busca em outro local se mostra como um importante registro de barreira de acesso à vacinação (19,20) , havendo nítido aumento da adesão quando este serviço é disponibilizado no próprio local de atendimento (21) .…”
Section: Introductionunclassified